Justice Denied: A Rawlsian Reading of To Kill a Mockingbird - Shrestha , Nokha Bahadur (Pragnya Sarathi, 2026)
This paper explores how justice as fairness fails in To Kill a Mockingbird written by American writer Harper Lee as seen from the point of view of John Rawls’s theory of justice, bringing the ideas from The Theory of Justice. The failure of Rawlsian principles of justice is a challenge to the democratic norms where the social and legal structures play role in victimizing the victims as seen in the character of Tom Robinson who has been accused of raping a girl without any proper evidences. While seeing through Rawls’s justice system, the society is to be guided by fairness, impartiality, and equality. However, this is not seen in the trial of Tom Robinson whose fundamental right has been violated as seen in the novel under scrutiny. Class systems and racial prejudices underestimate fair equality of opportunity causing Robinson’s death. The justice system substantively serves the people in higher status in the society. The impartial standpoint as imagined by Rawls’s “veil of ignorance” is lost in the trial tenure. One character representing Rawls’ veil of ignorance is while Atticus Finch with moral integrity, honesty, and rational fairness. His failure to secure justice despite being a lawyer is an outcome of racial tone which highlights Rawls’s claim that just outcomes are impossible.